(untitled) (Genius Repository, 2023)
The the article deals with the introduction of modern pedagogical technologies in the field of choreographic education and the results achieved with their help. The results of interactive lessons with students, a teacher of the subject "Methods of teaching Uzbek dance" were also described in detail.